Crimmigration and the prison: comparing trends in prison policy and practice in England & Wales and Norway - Pakes, Francis J. (European journal of criminology, 2017)
The crimmigration landscape in the UK is much lamented. Reference is frequently made to the recent creation of dozens of new immigration offences and a sharp increase in the administrative detention of immigrants during the last two decades. In particular, the prison has recently become an acute site of crimmigration, with separate prisons for foreign nationals (Kaufman, 2013). Norway, on the other hand, has traditionally been regarded as an exception. The treatment of criminals and outsiders is described as inclusive and rehabilitative and focused on their successful return to society. However, here a distinction is also increasingly made between prisoners who will return to society and those who will not, most particularly foreign nationals. The UK and Norway are virtually the only countries in Western Europe with regular prisons that are exclusively reserved for foreign nationals. This article examines how the arguably most benign and the arguably most severe prison systems of Western Europe have come to mimic each other in this fashion. Wider implications for our theoretical understanding of the nature and loci of crimmigration policies are also considered.